Where does global health funding come from and where does it go? - Germán Velásquez (South Centre, 2023)
In theory, the WHO is the coordinating agency for global health, and large private and public actors claim the relevance and central role of this UN agency. In practice, paradoxically, the money for health goes largely to other institutions and not to the WHO, or even new institutions or mechanisms are created where new funds are channeled (GAVI, Global Fund, Act-A, CEPI, COVAX, etc.) These institutions or mechanisms are, in most cases, public-private partnerships where the pharmaceutical industry is present. Official Development Assistance is important but represents only 1 per cent of what developing countries spend on health. What is actually spent to promote global health and where this money goes is the subject of this paper. One of the questions we must ask ourselves after the experience with COVID-19 is how will we preserve the global public interest by creating common public goods and protecting human rights in the prevention, preparedness and response to present and future pandemics.
Keywords: 300; Access to Medicines; Coalition for Epidemic Preparedness Innovations (CEPI); COVID-19; COVID-19 Vaccines Global Access (COVAX); GAVI the Vaccine Alliance; Global Health; Global Public Good; Health; Human Rights; Medicines Patent Pool (MPP); Official Development Assistance (ODA); Pan American Health Organization (PAHO); Pandemic; Pandemic Preparedness and Response; Pharmaceutical Industry; Public Interests; Public-Private Partnerships (PPPs); The Access to COVID-19 Tools (ACT) Accelerator; The Global Fund; The Pandemic Fund; UN Global Compact; UNAIDS; Unitaid; WHO Foundation; WHO Sustainable Financing Working Group; World Health Organization (WHO)